Spatial Equilibrium Analysis of Water Resources in Hubei Province and Countermeasures - TIAN Pei; ZHAO Zequn; MU Yaqing; FAN Yuyan; WU Guangdong; WANG Yongqiang; YU Yue (Renmin Zhujiang)
Water resources are important resources for social development. Revealing the characteristics of spatial equilibrium of water resources in Hubei Province can provide a basis for the sustainable utilization of water resources and economic development in Hubei Province. Three indexes of water resources including load index, water use efficiency, and agricultural water-soil matching coefficient were selected, and the Gini coefficient was used to calculate and analyze the equilibrium. The spatial equilibrium coefficient of water resources was utilized to reflect the overall equilibrium level of water resources in Hubei Province under the combined action of the three indexes, and the spatial equilibrium of water resources in Hubei Province was analyzed with the aid of transit water dependence. ① From 2010 to 2022, the overall load index (4.35~16.22) and water use efficiency (54.01~152.41) of water resources in Hubei Province showed an upward trend, while the agricultural water-soil matching coefficient (1.73~0.82) showed a downward trend. Economic development, population change, and cultivated land area were increasingly mismatched with water resources, but the utilization efficiency of water resources was gradually improved, and the level of economic development was conducive to improving the utilization efficiency of water resources. ② From 2010 to 2022, the spatial equilibrium of water resources in Hubei Province was gradually weakened. Affected by the disequilibrium of load index and agricultural water-soil matching coefficient of water resources, as well as the huge difference in the transit water dependence of each city, the matching between water resources endowment and the development of each city was gradually unbalanced. ③ Cities such as Wuhan, Yichang, and Xiangyang have a great influence on the spatial equilibrium of water resources in the region and the whole province. Therefore, Hubei Province should promote water-saving technology, improve water use efficiency, strengthen regional ties, accelerate resource equilibrium, actively introduce water diversion projects, and implement the development pattern of "one center and two wings". It is also necessary to strictly adhere to the red line of protecting cultivated areas of 1.8 billion mu while taking food sources from fields besides irrigation agriculture.